Development and feasibility testing of an oral hygiene intervention for stroke unit care. (16th May 2016) - Smith, Craig J.; Horne, Maria; McCracken, Giles; Young, David; Clements, Ian; Hulme, Sharon; Ardron, Claire; Hamdy, Shaheen; Vail, Andy; Walls, Angus; Tyrrell, Pippa J.
Abstract : Objective: To develop an oral hygiene complex intervention and evaluate its feasibility in a single UK stroke centre. Background: Oral hygiene interventions might improve clinical outcomes after stroke but evidence‐based practice is lacking. Materials and methods: We used a sequential mixed methods approach and developed an oral hygiene complex intervention comprising: (i) web‐based education and 'hands‐on' practical training for stroke unit nursing staff, (ii) a pragmatic oral hygiene protocol consisting of twice‐daily powered (or manual if preferred) brushing with chlorhexidine gel (or non‐foaming toothpaste) ± denture care. We evaluated feasibility of (i) the staff education and training and (ii) the oral hygiene protocol in consenting inpatients with confirmed stroke, requiring assistance with at least one aspect of personal care. Results: The staff education and training were feasible, acceptable and raised knowledge and awareness. Several barriers to completing the education and training were identified. The oral hygiene protocol was feasible and well‐tolerated. 22% of eligible patients screened declined participation in the study. Twenty‐nine patients (median age = 78 year; National Institutes of Health Stroke Scale score = 8.5; 73% dentate) were recruited at a median of 7 days from stroke onset. 97% of participants chose the default chlorhexidine‐based protocol; the remainder chose the non‐foaming toothpaste‐based protocol. The mouth hygiene protocol was administered as prescribed on 95% of occasions, over a median duration of 28 days. There were no adverse events attributed to the oral hygiene protocol. Conclusion: Our oral hygiene complex intervention was feasible in a single UK stroke centre. Further studies to optimise patient selection, model health economics and explore efficacy are now required.